A reduced risk of stroke with lithium exposure in bipolar disorder: a population‐based retrospective cohort study. (23rd September 2015) - Lan, Chen‐Chia; Liu, Chia‐Chien; Lin, Ching‐Heng; Lan, Tzuo‐Yun; McInnis, Melvin G; Chan, Chin‐Hong; Lan, Tsuo‐Hung
Abstract : Objectives: The risk of stroke is increased in patients with bipolar disorder. Lithium exhibits neuroprotective effects but the association between lithium use and the risk of stroke is unknown. Methods: A population‐based retrospective cohort study was conducted by utilizing the National Health Insurance Research Database in Taiwan. Subjects who had first been diagnosed with bipolar disorder between 2001 and 2006 were identified. A propensity score (PS) for receiving lithium was calculated with variables of age, gender, and comorbidities. The patients with bipolar disorder receiving lithium within the period from diagnosis through to December 2011 were designated as the lithium group (n = 635). A 1:2 ratio was used to select PS‐matched subjects with bipolar disorder without lithium use (n = 1, 250). Multivariate Cox proportional hazards regression models were used to explore the association, rather than causal inference, of lithium exposure and the risk of stroke. Results: Of the 1, 885 subjects, 86 (4.6%) experienced stroke, including 2.8% of the lithium group and 5.4% of the non‐lithium group. Lithium use was associated with a significantly reduced risk of stroke [hazard ratio (HR) = 0.39, 95% confidence interval (CI): 0.22–0.68]. Reduced risks of stroke were also associated with the highest cumulative lithium dose [≥720 defined daily dose (DDD), HR = 0.25, 95% CI: 0.10–0.59], the longest cumulative exposure period (≥720 days, HR = 0.20, 95% CI: 0.06–0.64), and the highest exposure rate (≥2 DDD/day, HR = 0.39, 95% CI: 0.21–0.70). Conclusions: Lithium use was significantly related to a reduced risk of stroke in patients with bipolar disorder.